Factors Affecting Youth's Social Image in the Globalization Period - Amonlaev Abdurasul Khakimovich (Zien Journals, 2022)
In this article, some considerations related to the discussion of current issues related to youth education in the era of globalization are put forward. In particular, the factors affecting the formation of the social image of young people were discussed, and the role of moral education and example in the fight against negative ideas spread through the Internet was discussed.
Keywords: youth; spirituality; example; Internet; upbringing